ISLAMIC EDUCATIONAL PERSPECTIVE ON QUR'ANIC VERSES SURAH AL-‘ALAQ 1-5 AND THEIR RELEVANCE TO ARTIFICIAL INTELLIGENCE CHALLENGES - Nanik Setyawati; Sulaeman Sulaeman; Mintaraga Eman Surya; Hafidz C. Pratama (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2025)
This study aims to analyse the meaning of QS. Al-‘Alaq verses 1–5 based on the contemporary interpretation of Tafsir Al-Misbah by M. Quraish Shihab as the basis for scientific ethics in Islamic education, as well as to examine its relevance to the development of science and ethics of artificial intelligence (AI) in the field of education. This study uses a qualitative method with a library research approach and thematic interpretation analysis (tafsir maudhu'i), which focuses on the integration of revelatory values and modern Islamic educational literature. The results show that QS. Al-‘Alaq 1–5 provides an epistemological and ethical foundation for Islamic education in addressing the challenges posed by AI. The command iqra' emphasises the importance of acquiring knowledge with divine consciousness; the term qalam represents an instrument of knowledge that must be directed towards benefit, while the phrase 'allama al-insān emphasises the dignity of humans as moral learners. Based on the maqasid al-syari'ah framework, the values of trust, justice, benefit, and respect for human dignity serve as the main principles for overcoming dehumanisation, algorithmic bias, privacy violations, and inequality in access to education. Thus, AI is positioned not as a substitute for human roles but as a means of strengthening ethical and spiritual literacy in the Islamic education system.